Ultraviolet B Treatment of the Forearm Alters Supraspinal Nociceptive Processing - Peter D. Drummond; Lechi Vo; Matthew Carabetta (Pain Research and Management)
Exposing the skin to high levels of ultraviolet B (UVB) radiation induces an inflammatory response that upregulates local nociceptive processing; this, in turn, facilitates protective responses to limit further injury. In this study, the UVB model was used to explore additional effects of inflammation on supraspinal nociceptive processing. Thirty-one healthy participants attended two sessions approximately 24 h apart. In each session, pressure-pain thresholds and sensitivity to sharp stimulation and heat were assessed in both forearms, and pressure-pain thresholds and sensitivity to sharp stimulation were assessed on each side of the forehead. In a novel paradigm, supraspinal nociceptive processing was explored by assessing pain and blink reflexes to electrical stimulation of the forehead, paired with acoustic startle stimuli. At the end of the first session, UVB radiation at a dose sufficient to induce erythema at the most exposed site was administered to one forearm. Consistent with local sensitization, sensitivity to heat and sharp stimulation had increased at the maximally exposed site 24 h later. This local response was accompanied by changes in supraspinal nociceptive processing—pressure-pain thresholds were lower on the ipsilateral than contralateral side of the forehead, and acoustic startle stimuli augmented electrically evoked pain. Blink reflexes weakened from the first to the second session, but decreases were smaller on the UVB-treated than contralateral side. Together, these findings suggest that acoustic startle stimuli facilitated activity in sensitized supraspinal nociceptive pathways. Potentially, this supraspinal mechanism adds to the burden of chronic nociplastic pain during states of heightened arousal and stress.